Research and development of energy from biomass in Malaysia - Megat Mohd Noor, Megat Johari; Baharin, Badlishah Sham (2012)
Energy is readily consumed at a rapid rate. Our present stocks and sources of energy will not last forever. In fact,petroleum feedstocks are estimated to last only a few decades more. Therefore,alternative sources of energy has to be discovered and harnessed to its full potential as a supplier of enrgy to mankind. One of the chief alternative sources of energy is biomass. It is abundant,readily available and has the natural capacity to produce energy. What remains to be seenis the technology to harness this energy and convert it to a viable commercial operation. Until now,production of alcohol from carbohydrate substrate,palm diesel for palm oil and others have been achieved. Further research ansdevelopment has to be carried out to look at other substrates and even genetic manipulation to produce a breed of microorganisms that can harness this great energy potential. Last but not least,mankind has to got to realise and change their attitude that the age of biomass has arrived.